Media representation, image, brand of the country: essence and meaning - Abylkhanova, Ә.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article describes origins of the concepts of representation, image, brand, and its area of use in details. Although Russian scholars have argued that it is necessary to be able to distinguish these concepts without using them interchangeably, it has become clear that, according to the nature of the study, they can sometimes be used interchangeably. However, in the context of the representation / image of the state, it was found that concepts of «image» and «representation are used together in scientific works that aim to study situations in which a country attempts to form its positive image in the domestic and international space. In addition, concepts of image / brand are often considered in tandem rather than in complex. For instance, representation / image and image / brand. A» representation» is associated with an existing, self-reproducing image, «image» is an existing but constructed image, and «brand» is used in the field of economics, tourism, and marketing. The main purpose of the article is to identify the roots of the concepts of obraz / image / brand of the state and their meanings. This is because the correct use of the concept when writing a research paper will help clarify the heart of the matter. In this regard, the study analyzed in detail the work of a number of Russian scientists who took part in a deeper study of the use of these terms. In particular, E. Shestopal, I.V. Sidorskaya, A.A. Graver, E. Galumov AP Pankrukhin, A. Ignatievs comprehensively revealed the concepts of the state image and brand. The article presents a content analysis of news from BBC.com, one of the world’s largest news agencies. During the analysis, special attention was paid to the materials written about Kazakhstan on the website and their content. In addition, the article describes the impact of negative publications on the state image of Kazakhstan